The moderating effect of project risk mitigation strategies on the relationship between delay factors and construction project performance - Zailani, S.; Ariffin, H.A.M.; Iranmanesh, M.; Moeinzadeh, S.; Iranmanesh, M. (Emerald, 2016)
Purpose: This paper aims to explore the relationship between delay factors and construction project performance with respect to project risk mitigation strategies as moderators. Design/methodology/approach: Random sampling was used to select the sample of the study. Data were gathered through a survey of 204 Malaysian construction companies. The data were analysed using the partial least squares technique. Findings: The results indicate that environmental, resource and coordination issues negatively affect construction project performance. Project visibility and flexibility can mitigate the negative effects of both resource and coordination issues on project performance. Furthermore, supplier development can mitigate the negative effects of coordination issues. Practical implications: The findings of the study will be useful for construction firms to complete construction projects timely, within a scheduled budget and with only minor defects if adopted. Originality/value: This study is among the first to empirically test the moderating role of risk mitigation strategies on the relationship between delay factors and project performance in the construction industry.